The Domestic Role of Men in the Qur'an (Comparative Study of the Interpretation of Imam Al-Tabari and Zainab Al-Ghazali ) - Lumanatul Latifah; Fauzi Fathur Rosi (Penerbit Hellow Pustaka, 2024)
In Indonesia generally, parents or the environment indirectly differentiate the roles of boys and girls. Demands for gender equality are starting to reverberate because more parties feel the need to voice this issue. Seeing this phenomenon, it is important to know how the role of men where Al-Tabari represents classical interpretation and Zainab al Ghazali represents contemporary interpretation. This study uses a qualitative approach with the type of library research. The results of this study indicate that Imam al-Tabari interprets that men are responsible for women because men are more important than women, men's priority is because they provide dowry and maintenance, whereas according to Zainab al-Ghazali Allah SWT determines men to be responsible for women, and they have the right to lead and be guardians in the family. The difference between al-Tabari and Zainab Al-Ghazali lies in the interpretation in dealing with wives who are nushuz, that is, if they don't change after being given advice, according to al-Tabari if they don't change, confine them to their place of residence, whereas according to Zainab Al- Ghazali if it doesn't change after being given advice then ignore it by separating beds.